The Holy Spirit - Michael, Matthew (Christian Theology and African Traditions, 2013)
The Pentecostal movement has brought to the fore the reality of the person, work and ministry of the Holy Spirit to the modern consciousness in the face of increasing secularization of the modern world and its attending anti-supernatural presuppositions.¹ This reawakening of the significance of the Holy Spirit in the life of the church arose out of certain factors. The key factor is the growing coldness of the mainline churches who often refuse to recognize or allow the free operation of the Holy Spirit in the church’s life.² This neglect of the active presence of the Holy Spirit often leads
Paid